ENDOSCOPIC SCLEROTHERAPY OF ESOPHAGEAL VARICES INCREASES GASTROESOPHAGEAL REFLUX - S. KAYMAKOĞLU; G. BOZTAŞ; Z. MUNGAN; S. ÖZDİL; I. ADALET; Y. ÇAKALOĞLU; F. BEŞIŞIK; O. YEĞİNSÜ; N. EROL; A. ÖKTEN; R. SEZER (Turkish Journal of Gastroenterology, 2020)
-